2023
DOI: 10.3389/fendo.2023.1162158
|View full text |Cite
|
Sign up to set email alerts
|

Asthma prevalence is increased in patients with high metabolism scores for visceral fat: study reports from the US

Abstract: ObjectiveData from NHANES 2001-2018 were used to examine the relationship between metabolism score for visceral fat (METS-VF) and asthma prevalence.MethodsWe assessed the association between METS-VF and asthma disease using multiple logistic regression analysis from the National Health and Nutrition Examination Survey (NHANES), 2001-2018, followed by subgroup analysis for sensitive populations. To determine whether METS-VF and asthma disease had a non-linear relationship, smooth curve fitting was used, and thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In agreement with the two aforementioned studies, the Nord-Trøndelag Health Study (HUNT) examining prospectively 23191 adults aged 19-55 years, without asthma at baseline, showed that metabolic syndrome was related to increased risk of incident asthma, indicating that physicians may take metabolic syndrome into account as a predictor of future risk of asthma [76]. The same was the result from another study that used multiple logistic regression analyses from the National Health and Nutrition Examination Survey (NHANES), 2001-2018, and found that an increase in the metabolism score for visceral fat (METS-VF) index was related to an increase in the incidence of asthma [77]. Recently, a cross-sectional analysis of 41,480 adults from the Korean National Health and Nutrition Examination Survey during the period 2007-2016, revealed that when both obesity and metabolic syndrome are present, the risk of developing asthma is highest [78].…”
Section: Epidemiological-observational Studiesmentioning
confidence: 70%
“…In agreement with the two aforementioned studies, the Nord-Trøndelag Health Study (HUNT) examining prospectively 23191 adults aged 19-55 years, without asthma at baseline, showed that metabolic syndrome was related to increased risk of incident asthma, indicating that physicians may take metabolic syndrome into account as a predictor of future risk of asthma [76]. The same was the result from another study that used multiple logistic regression analyses from the National Health and Nutrition Examination Survey (NHANES), 2001-2018, and found that an increase in the metabolism score for visceral fat (METS-VF) index was related to an increase in the incidence of asthma [77]. Recently, a cross-sectional analysis of 41,480 adults from the Korean National Health and Nutrition Examination Survey during the period 2007-2016, revealed that when both obesity and metabolic syndrome are present, the risk of developing asthma is highest [78].…”
Section: Epidemiological-observational Studiesmentioning
confidence: 70%
“…Additionally, in comparison to other evaluation indicators of obesity, METS-VF demonstrates reliability and applicability as a predictor of hypertension and diabetes within the Chinese population [ 44 , 45 ]. A 36,876-person study found a favorable correlation between METS-VF and asthma [ 21 ]. For non-obese women, the METS-VF is helpful in directing the prevention and management of hyperuricemia [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The formulas pertaining to these measures are presented in the following manner. Gender was presumed to be 1 because there were no female participants in this study [ 19 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…METS-VF is closely associated with metabolic diseases, and is a reliable predictor for the development of type 2 diabetes (AUC: 0.690, 95% CI: 0.682–0.698), metabolic syndrome (AUC: 0.952, 95% CI: 0.951–0.953), non-alcoholic fatty liver disease (NAFLD) (AUC: 0.812, 95% CI: 0.802–0.823), and chronic kidney disease (AUC: 0.634, 95% CI: 0.589–0.680) [ 10 13 ]. Moreover, METS-VF exhibits a robust association with several diseases, including kidney stones, asthma, hypertension, and hyperuricaemia [ 14 17 ].…”
Section: Introductionmentioning
confidence: 99%